SPIRITUAL SUPPORT FOR SYNOVIAL SARCOMA WITH GRIEF AND LOSS: BARGAINING PHASE - Wijanarko, Firdausan Miloni; Hidayah, Ridhoyanti (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Synovial sarcoma is a rare high-grade soft tissue tumor, which is about 5% to 10% of the total soft tissue sarcoma and can occur at various ages. The prognosis in patients with synovial sarcoma is influenced by many characteristics of the disease, namely tumor size, invade locality, histologic type, presence of metastases and lymph node involvement, and successful surgery. Surgery can have an impact, namely the problem of grieving in sufferers. Spirituality is an important indicator of quality of life and an aspect that reduces the negative impact of an ineffective grieving process. In helping patients cope with grieving responses, spiritual support is provided not only by religious practices. Spiritual support also refers to activities that provide a calm atmosphere, provide entertainment, listen to patients, provide and respect privacy, and support patients' search for meaning and purpose in life. Objective: The aim of the research was to apply nursing care which includes assessment, determination of diagnoses, interventions based on evidence-based practice, implementation and evaluation of nursing. Methods: The research methods used are interviews, observation and documentation studies. The design of this research is a case study with synovial sarcoma patient respondents who were given spiritual support nursing interventions. Result: Based on the results of the nursing evaluation, there was a decrease in the level of grieving in patients after being given spiritual support. Conclusion: Thus, the patient's care plan is continued by the ward nurse and encourages the patient and family to use spiritual support as a step to overcome feelings of grief.